Navigating the political minefield: strategies for online participation in a polarized society - Ziv, Limor; Yavetz, Gal (Frontiers in Communication, 2025)
In this study, we explored political participation among young adults in Israel, with a particular focus on the impact of polarization on their engagement in online discourse. To this end, by extracting a total of 23,223 Facebook activities (e.g., likes, comments) from 50 participants, we analyzed 2,323 partisan-political and 1,434 socio-political patterns in political and social identity expressions. In contrast to previous research that predominantly relied only on self-report or observed activities, we used direct activity logs, combined with in-depth interviews, thereby obtaining a more detailed insight into user behavior. The results revealed that Facebook usage frequently reflects a hidden “political self,” characterized by non-committal interactions (e.g., frequent likes). The study participants were more at ease within the socio-political domain than in partisan-political discussions. We also found that young adults use social media to cautiously navigate their political and social identities in polarized settings. Based on the results, we propose a novel framework for the analysis of social media engagement that could be useful for policymakers, politicians, and social organizations in crafting strategies to target young adults. The study concludes with the discussion of the necessity to confront polarization by promoting a balanced approach to digital discourse among young adults.